Young Couples and Unintended Pregnancy Risk - Firdawsyi Nuzula; Maulida Nurfazriah Oktaviana (Discover Health and Medicine, 2025)
Introduction: Teenage pregnancy is a global phenomenon with well-established causes and serious health, social, and economic consequences for individuals, families, and communities. Pregnancy at a very young age correlates with higher maternal and fetal morbidity and mortality rates. Methods: This study employed a cross-sectional design with a simple random sampling technique. Bivariate analysis was conducted using the chi-square test, while multivariate analysis used logistic regression. Results: The chi-square test results showed p-values for education (0.875), occupation (0.075), knowledge (0.279), culture (0.026), and parenting style (0.039). Logistic regression analysis revealed that cultural factors had a significance value of 0.020 with an odds ratio (OR) of 6.072, while parenting style had a significance value of 0.047 with an OR of 2.223. Conclusion: Cultural factors are six times more likely to influence early pregnancy compared to parenting style, which increases the risk twofold. Culture plays a dominant role in early marriage and teenage pregnancy due to the persistence of traditional and social norms, particularly in rural communities.